Three‐dimensional mapping of the orientation of collagen corneal lamellae in healthy and keratoconic human corneas using SHG microscopy. Issue 1 (29th July 2016) - Mercatelli, Raffaella; Ratto, Fulvio; Rossi, Francesca; Tatini, Francesca; Menabuoni, Luca; Malandrini, Alex; Nicoletti, Riccardo; Pini, Roberto; Pavone, Francesco Saverio; Cicchi, Riccardo
Abstract : Keratoconus is an eye disorder that causes the cornea to take an abnormal conical shape, thus impairing its refractive functions and causing blindness. The late diagnosis of keratoconus is among the principal reasons for corneal surgical transplantation. This pathology is characterized by a reduced corneal stiffness in the region immediately below Bowman's membrane, probably due to a different lamellar organization, as suggested by previous studies. Here, the lamellar organization in this corneal region is characterized in three dimensions by means of second‐harmonic generation (SHG) microscopy. In particular, a method based on a three‐dimensional correlation analysis allows to probe the orientation of sutural lamellae close to the Bowman's membrane, finding statistical differences between healthy and keratoconic samples. This method is demonstrated also in combination with an epi‐detection scheme, paving the way for a potential clinical ophthalmic application of SHG microscopy for the early diagnosis of keratoconus.SHG image acquired with sagittal optical sectioning (A ) of a healthy cornea and (B ) of a keratoconic cornea. Scale bars: 30 μm. Abstract : Keratoconus is an ophthalmic disease consisting in an abnormal conical shape of cornea that causes visual impairment. A cross‐correlation analysis performed on SHG images allowed diagnosing keratoconus against healthy cornea on the basis of the inclination of corneal lamellae. For the first time, the analysis was carried out in conjunction with epi‐detection, paving the way for the ophthalmic clinical use of SHG microscopy.